Phytoplankton diversity and occurrence of Raphidiopsis raciborskii (Woloszynska) in the Jequiá Estuarine Lagoon System (Alagoas, Brazil) - Marinho de Melo-Magalhães, Enaide; Gomes de Souza, Clyvia Roberta; Campos de Andrade Lima, Rochana (Arquivos de Ciências do Mar, 2023)
The Jequiá Lagoon is the third largest on the Alagoas coast, it is located between the geographic coordinates 9°50’-10°50’S and 36°00’-36°10’W. The present study aimed to contribute to the knowledge of the planktonic microflora, approaching the qualitative and quantitative aspects, in addition to verifying the occurrence of potentially toxic cyanobacteria in the Jequiá Lagoon Estuarine System. Samples for qualitative and quantitative analysis were collected in October and December 2019 at four stations. For phytoplankton quantification, samples were made directly from the subsurface of the water and fixed with lugol. For the qualitative study, the samples were obtained using a plankton net with 25µm mesh and fixed with 4% neutralized formaldehyde. It was identified 72 taxa represented mainly by freshwater species, standing out in qualitative terms, the groups Heterokontophyta, Cyanophyta and Chlorophyta. Phytoplankton density varied from 37,560 to 146,800 Org.mL-1. The most abundant and frequent species was the cyanobacteria Raphidiopsis raciborskii (Woloszynska) with densities varying from 28,140 Org.mL-1 to 142,720 Org.mL-1. The dominance of the cyanobacterium R. raciborskii contributed to the low values of phytoplankton diversity and evenness at sampling stations. Keywords: estuary, plankton, ecology, tropical ecosystem.